Physical Activity Levels among Preschool-Aged Children in Family Child Care Homes: A Comparison between Hispanic and Non-Hispanic Children Using Accelerometry - Augustine W. Kang; Kim M. Gans; Tayla von Ash; Danielle Castagneri; Laura Dionne; Alison Tovar; Patricia M. Risica (MDPI AG, 2021)
Obesity prevalence among Hispanic children is twice that of non-Hispanic white children; Hispanic children may also engage in less physical activity (PA) compared to non-Hispanic white children. A large number of U.S. preschool-aged children are cared for in Family Child Care Homes (FCCH), yet few studies have examined PA levels and ethnicity differences in PA levels among these children. We examine baseline data from a cluster-randomized trial (Healthy Start/Comienzos Sanos) to improve food and PA environments in FCCHs. Children aged 2-to-5-years (n = 342) wore triaxial accelerometers for two days in FCCHs. Variables examined include percentage of time (%) spent in sedentary, and light, moderate, and vigorous PA. The full dataset (n = 342) indicated sedentary behavior 62% ± 11% of the time and only 10% ± 5% of the time spent in moderate-to-vigorous PA. Among children in the upper-median half of wear-time (n = 176), Hispanic children had significantly greater % sedentary time vs. Non-Hispanic children (66.2% ± 8.3% vs. 62.6% ± 6.9%, p = 0.007), and lower % light PA (25.4% ± 6.3% vs. 27.7% ± 4.9%, p = 0.008) and moderate PA (5.5% ± 2.1% vs. 6.4% ± 2.2%, p = 0.018). Our results highlight that PA levels were lower among our sample compared to previous studies, and that Hispanic children were more sedentary and less active compared to non-Hispanic white children.